Confounding effects of gavage in mice: Impaired respiratory structure and function - Larcombe, Alexander; Wang, K.C.W.; Phan, J.A.; Berry, L.J.; Noble, P.B. (AMER THORACIC SOC, 2019)
The authors talk about the confounding effects of gavage in mice. He said that gavage is the most widely used method for precise oral dosing in experimental studies involving rodents. In the hands of a skilled operator, the procedure is rapid and allows for a precise volume of a substance to be delivered directly to the stomach, where it can be absorbed. Gavage is advantageous in situations where the substance to be delivered cannot be incorporated into feed or is unpalatable. Of particular interest to the current readership is the common use of gavage in studies with a respiratory focus.